Increased Pain Sensitivity in Obese Patients After Lung Cancer Surgery - Majchrzak, Maciej; Brzecka, Anna; Daroszewski, Cyryl; Błasiak, Piotr; Rzechonek, Adam; Tarasov, Vadim V.; Chubarev, Vladimir N.; Kurinnaya, Anastasiya S.; Melnikova, Tatiana I.; Makhmutova, Alfiya; Klochkov, Sergey G.; Somasundaram, Siva G.; et al. (Frontiers in Pharmacology, 2019)
BACKGROUND. Obesity and cancer are recognized worldwide health threats. While there is no reported causal relationship, the increasing frequency of both conditions results in a higher incidence of obese patients who are being treated for cancer. Physiological data indicate there is a relationship between obesity and susceptibility to pain; however, currently there are no specific pharmacological interventions. OBJECTIVE. To evaluate the self-reported intensity of postoperative pain in obese and non-obese lung cancer who receive either thoracotomy or VATS surgical therapy. MATERIAL AND METHODS. In 50 obese [mean Body Mass Index (BMI) of 34.1±3.2 kg/m2] and 62 non-obese (mean BMI of 24.9±3 kg/m2) lung cancer patients, the intensity of pain was estimated every four hours using a Visual Analog Scale (0 indicating no pain and 10 indicating “worst imaginable pain”) beginning shortly after surgery (Day O) and continuing until the day of discharge (Day D). RESULTS. The self-reported pain was more severe in obese than in non-obese patients, both at the time of the operation [Day O (4.5±1.2 vs 3.4±1.1; p<0.0001)] and at the day of discharge [Day D (3.9±1.4 vs 2.6±0.9, p<0.0001)]. This finding was consistent both in the patients after thoracotomy and after Video-Assisted Thoracic Surgery (VATS, p<0.0001). The patients with severe pain shortly after surgery (VAS score >4) had significantly higher BMI (31.8±5.6 kg/m2 vs 28.8±5.2 kg/m2, p<0.01) and were hospitalized longer than the remaining patients (13.0±13.6 days vs 9.5±3.6 days, p<0.05). CONCLUSION. The reported perception of pain in obese lung cancer patients is greater than non-obese patients undergoing the same thoracic surgery. In obese patients severe pain persisted longer. Pain management is an important consideration in the postoperative care of lung cancer patients, even more so with obese patients.